Translation Analysis in a Children's Storybook Entitled The Rainbow Fish - Mumtahanah, Qonita; Manggarrani, Maria Dita (Universitas Syiah Kuala, 2025)
This study analyzes the translation shifts and translation methods applied in the children's storybook